Leopards in the City: The Tale of Sanjay Gandhi National Park and Tungareshwar Wildlife Sanctuary, Two Protected Areas in and Adjacent to Mumbai, India - Surve, Nikit Sanjay; Sathyakumar, Sambandam; Sankar, Kalyanasundaram; Jathanna, Devcharan; Gupta, Vikas; Athreya, Vidya (Frontiers in Conservation Science, 2022)
Recent studies in the last decade have recorded obligate carnivores adapting to human dominated landscapes. Leopards, amongst other large carnivores, are highly adaptable and survive in a range of environments from the arid regions of Africa and the Middle East to the cold regions of the Russian Far East. They are also highly adaptable in their diet and consequently are present close to and even within high-density human landscapes. These also include the edges of urban areas such as Nairobi and Mumbai. Our study, to better understand the coexistence of leopards and humans, was conducted in 104 km2 of Sanjay Gandhi National Park (SGNP), which is surrounded on three sides by the urban landscape of Mumbai and Thane cities. The study area also included 85 km2 of an adjoining protected area, Tungareshwar Wildlife Sanctuary (TWLS), which is surrounded by a combination of forests, rural areas and agricultural lands. Based on spatial capture - recapture framework we observed that leopard densities in SGNP (26.34 ± 4.96 leopards/100 km2) and TWLS (5.40 ± 2.99 leopards/100 km2) were vastly different. We found that density estimates of wild prey and domestic dogs were higher in SGNP in comparison to TWLS. In both the protected areas (PAs), domestic dogs formed a major proportion of leopard diet and were the single highest species contributors. Our study shows that despite extremely high human density around SGNP (~20,000 people/km2), leopard density is also much higher than the adjoining TWLS which has a comparatively lower surrounding density of people (~1,700 people/km2). Leopard density reported from SGNP is amongst the highest ever reported. This interesting result is probably due to much higher biomass of potential food resources in and around SGNP. Studying this relationship between leopards and their prey (both wild and domestic) in a human dominated landscape will give us valuable insights on human - leopard interactions. The two adjacent and connected PAs are similar ecologically, but differ widely in almost all other aspects, including human densities along the periphery, leopard densities, prey densities as well as management regimes.